Muslims' religiosity and views on religion in six Western European countries: does national context matter?. Issue 2 (26th January 2016) - Torrekens, Corinne; Jacobs, Dirk
ABSTARCT: This article investigates the impact of discursive and political opportunity structures on religiosity among Muslims and on perceived distance between Muslims and non-Muslims on the role of religion in society, making use of the EURISLAM-data-set (2010). We will focus on Moroccan, Turkish, Pakistani and ex-Yugoslavian origin samples of migrants of Muslim origin and a control group of non-Muslim majority group citizens for six participating countries (Belgium, France, Germany, the Netherlands, Switzerland and the UK). Our analysis does not show any impact of opportunity structures on Muslims religiosity nor on perceived differences between Muslims and non-Muslims.